A conceptual framework for predicting the effects of encroachment on magnitude of flood in Foma-river area, Kwara State, Nigeria using data mining - Chindo, A.A.; Mohd Shaharanee, Izwan Nizal; Mohd Jamil, Jastini (2019)
Flooding occurs but there is no flood hazard. It is only after human encroachment into the floodplain that turn into hazard. The practice of continuous increase of properties development along the floodplain and indiscriminate refuse disposal into water channels have been a major constituting factors to intensive flooding along the floodplain. This is as a result of decline in the capacity of floodplain to absorbs excess flooding, thus resulting to exposing more urban areas to be vulnerable to flood. Foma-river is located in Ilorin Kwara, Nigeria on latitude N08,49574 and longitude E004,5107. Climate of Ilorin comprises of the dry and wet seasons with the wet season starting around March and lasting for about four to five months. This study intends to propose a conceptual framework to support the prediction of effects of season on magnitude of flood in Foma-river area using data mining approach based on 7 years sampled data from Nigeria Meteorological Agency (NIMET), and questionnaire responses from residents along Foma-river floodplain